Mengisi Kekosongan Jabatan Wakil Kepala Daerah dan Undang-Undang Nomor 32 Tahun 2004 Juncto Undang-Undang Nomor 12 Tahun 2008 - Valerie Alexia; Maharani Nurdin (Jurnal Ilmiah Wahana Pendidikan, 2023)
If Indonesia returns to its previous form of local government, a deputy regional head will be appointed, with the power and task of realizing regional development and sustainability. Definition of key concepts in decentralized social theory. Due to the merger of Local Government Regulation Number 32 of 2004 with Local Government Law Number 12 of 2008 with Local Government Law Number 10 of 2004 with Amendments to Local Government Law Number 12, the provision of this welfare is not supported by good local government laws. Ultimately, it is important to stimulate the involvement of public officials in the application of relevant laws and to control the maximum term of office of the deputy governor under Indonesian local government laws. Realizing the objectives of the national vision of Pancasila Law, namely the enforcement of justice, the maintenance of legal clarity, and the protection of legal interests.